Pengembangan Buku Siswa Dengan Pendekatan Pendidikan Matematika Realistik (PMR) Pada Topik Garis Dan Sudut Di SMP - Wardhani, Indah Setyo (STKIP PGRI TULUNGAGUNG, 2013)
This study aimed to develop studentsâ€™ texook on the topic of line and angle for junior high school by using PMR approach. The background of this study was the students difficulty in mastering the concept of line and angle. The researcher developed teaching instrument in the form of textookÂ applying PMR approach. This approach emphasized on the use of mathematics in real life experience and it was the reason of the researcher chose the approach. This step of this study were situational analysis developing the planning of the draft of textook, material development, validating. The product try out stated that the first evaluation showed the average of individual score was 78,63. Meanwhile, the second evaluation was 88,37. By developing this textook, it was expected that the students would e active to construct their knowledge on the topic of line and angle.